2020
DOI: 10.1097/mpg.0000000000003002
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Diagnosis of Eosinophilic Esophagitis and Inflammatory Bowel Disease in the Pediatric Population

Abstract: Background and Aims: The incidence and prevalence of eosinophilic esophagitis (EoE) and inflammatory bowel disease (IBD) are rising with similar patterns. Co-occurrence of both diseases in the same patient has been increasingly reported. We sought to examine the pediatric population with both EoE and IBD to better understand the epidemiology and clinical implications of this overlap. Methods: We conducted a retrospective case-control study at 2 tertiary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 19 publications
1
25
2
Order By: Relevance
“…They noted that the rate of EoE diagnosis per initial EGD increased 4-fold for CD and 5-fold for UC between 2009 and 2016 even though the number of EGD's remained stable, suggesting that the number of patients with EoE and IBD is increasing faster for UC than CD. Moore et al (10) described 67 pediatric patients with EoE and IBD from a population of 4515 IBD patients and 3053 EoE patients (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). The prevalence of IBD in the EoE population was 2.2% and EoE in the IBD population was 1.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They noted that the rate of EoE diagnosis per initial EGD increased 4-fold for CD and 5-fold for UC between 2009 and 2016 even though the number of EGD's remained stable, suggesting that the number of patients with EoE and IBD is increasing faster for UC than CD. Moore et al (10) described 67 pediatric patients with EoE and IBD from a population of 4515 IBD patients and 3053 EoE patients (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018). The prevalence of IBD in the EoE population was 2.2% and EoE in the IBD population was 1.5%.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported an association of EoE and IBD (8,10–13). In this single center study, we found 8.8% of our IBD population had EoE and 9.4% of our EoE patients had IBD.…”
Section: Discussionmentioning
confidence: 99%
“…Among our cohort, 5 patients had concurrent EoE and IBD, including one patient with CGD SCID, CVID, and IPEX and one within the "other" category. EoE is increasingly recognized to co-occur with inflammatory bowel disease (38)(39)(40), and in some cohorts, the patients are more likely to be male, present at a younger age, and be associated with comorbid atopic disorders (41). It is important to note that mucocutaneous candidiasis can cause secondary gastrointestinal eosinophilia (13,27,28).…”
Section: Discussionmentioning
confidence: 99%
“…The recent retrospective case-control study found the prevalence of IBD among pediatric EoE patients to be significantly higher than EoE and IBD alone in the general population (2.2% compared to 0.4% in the general population). 7 This association and other etiologies of rectal bleeding prompted the clinical team to proceed with colonoscopy, leading to the diagnosis of HGM in the rectum. Clinical features of HGM can mimic IBD and may be difficult to differentiate without histological evaluation.…”
Section: Discussionmentioning
confidence: 99%